Home buyouts and household recovery: neighborhood differences three years after Hurricane Sandy. (15th March 2019) - Binder, Sherri B.; Barile, John P.; Baker, Charlene K.; Kulp, Bethann
ABSTRACT: Home buyout programs facilitate the permanent relocation of residents away from areas considered to be at risk from future hazards, though few studies have examined the impacts of home buyout programs on affected households and communities beyond the program implementation period. In this paper, we examine between-neighborhood variation in key recovery indicators for three neighborhoods that followed different paths to recovery after Hurricane Sandy: one that rebuilt in situ, one that participated in a buyout and relocated, and one located immediately adjacent to the buyout zone. Three years post-disaster, buyout participants are faring worse in terms of place attachment and social capital compared to residents in the other two neighborhoods, while the neighborhood adjacent to the buyout zone is also showing signs of decline. These findings suggest that the social costs of buyouts extend well into the recovery period, and that the place-based ties and social networks that would typically help individuals cope with disaster impacts and persevere through adversity may be diminished for buyout participants, ultimately hindering their recovery. We conclude with a discussion of the implications of buyouts on participating and affected communities, as well as implications for research and policy.